2015
DOI: 10.1007/s12272-015-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anticholinesterase activity of six flavonoids isolated from Polygonum and Dorstenia species

Abstract: This study was aimed at investigating the anti-inflammatory and anticholinesterase activity of six naturally occurring flavonoids: (-) pinostrobin (1), 2',4'-dihydroxy-3',6'-dimethoxychalcone (2), 6-8-diprenyleriodictyol (3), isobavachalcone (4), 4-hydroxylonchocarpin (5) and 6-prenylapigenin (6). These compounds were isolated from Dorstenia and Polygonum species used traditionally to treat pain. The anti-inflammatory activity was determined by using the Griess assay and the 15-lipoxygenase inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The reported concentrations of the FOX reagent components vary in literature for both the ferrous salt and xylenol orange (Dzoyem, Kuete, McGaw, & Eloff, ; Dzoyem, Nkuete, Ngameni, & Eloff, ; Gay & Gebicki, ; Orefice et al., ; Santas, Guzmán, Guardiola, Rafecas, & Bou, ; Timabud, Sanitchon, & Pongdontri, ). The acidic medium is crucial for the assay, with a value of 1.8 being reported as optimal (Gay, Collins, & Gebicki, ; Gay & Gebicki, ; Timabud et al., ), and usually, sulphuric acid 25 mM (Dzoyem et al., ; Gay et al., ; Nourooz‐Zadeh, ; Santas et al., ) or perchloric acid 110 mM (Gay & Gebicki, ; Orefice et al., ; Timabud et al., ) is chosen as reagent solvent. For the formation of the detectable complex, an incubation step is required, from 5 (Mehta et al., ) up to 30 min (Marasca, Greetham, Herring, & Fisk, ; Santas et al., ), being detectable at either 530 (Bilgili et al., ), 550 (Timabud et al., ), or 560 nm (Gay & Gebicki, ; Gay et al., ; Santas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported concentrations of the FOX reagent components vary in literature for both the ferrous salt and xylenol orange (Dzoyem, Kuete, McGaw, & Eloff, ; Dzoyem, Nkuete, Ngameni, & Eloff, ; Gay & Gebicki, ; Orefice et al., ; Santas, Guzmán, Guardiola, Rafecas, & Bou, ; Timabud, Sanitchon, & Pongdontri, ). The acidic medium is crucial for the assay, with a value of 1.8 being reported as optimal (Gay, Collins, & Gebicki, ; Gay & Gebicki, ; Timabud et al., ), and usually, sulphuric acid 25 mM (Dzoyem et al., ; Gay et al., ; Nourooz‐Zadeh, ; Santas et al., ) or perchloric acid 110 mM (Gay & Gebicki, ; Orefice et al., ; Timabud et al., ) is chosen as reagent solvent. For the formation of the detectable complex, an incubation step is required, from 5 (Mehta et al., ) up to 30 min (Marasca, Greetham, Herring, & Fisk, ; Santas et al., ), being detectable at either 530 (Bilgili et al., ), 550 (Timabud et al., ), or 560 nm (Gay & Gebicki, ; Gay et al., ; Santas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested some pharmacological activity for pinocembrin and pinostrobin including anti-cancer, antiinflammatory, anti-diabetic, and anti-oxidant activities (15)(16)(17)(18)(19)(20)(21)(22)(23). Understanding the role of each flavonoid enantiomer in the pharmacological activity described for the racemic mixtures is important as the combined effect of some enantiomers can be exaggerated or attenuated.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds of chalcones were discovered to strongly inhibit nitric oxide (NO), IL-6, and prostaglandin E 2 (PGE 2 ) secretion. On one hand, echinatin, licochalcones A-E, isobavachalcone, morachalcone A, DTM, licoagrochalcone C, and 4-hydroxylonchocarpin have been demonstrated to show significant inhibitory activity on LPSinduced NO production [10,21,69,70,78,80]. On the other hand, these compounds also have other different anti-inflammatory mechanisms.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%